Analisis Yuridis Pembentukan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja terhadap Penerapan Omnibus Law Perspektif Siyāsah Dustūriyyah - Nasution, Soleh; Irwansyah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
Law Number 11 of 2020 concerning Job Creation is the first legal product in Indonesia that uses the omnibus law method. This study aims to analyze the juridical aspects of the formation of the Job Creation Law and the application of the omnibus law concept in the perspective of siyāsah dustūriyyah (Islamic constitutional law). The research method used is normative legal with a statute approach, conceptual approach, and comparative approach. Secondary data was obtained through a literature study of primary, secondary, and tertiary legal materials, then analyzed qualitatively using descriptive-analytical techniques. The results of the study show that, legally, the formation of the Job Creation Law encountered various procedural problems that conflicted with Law Number 12 of 2011 concerning the Formation of Legislation, particularly regarding public participation, clarity of academic texts, and substance harmonization. From a constitutional perspective, the concept of omnibus law is acceptable as long as it is in accordance with the principles of maslahah mursalah (public interest), justice (al-'adalah), deliberation (asy-syura), and does not conflict with maqashid syariah (sharia objectives).